Neurotoxic envenoming by the Sri Lankan krait (Bungarus ceylonicus) complicated by traditional treatment and a reaction to antivenom. - de Silva, A; Mendis, S; Warrell, D (1993)
A 30 year old woman bitten by a large Sri Lankan krait (Bungarus ceylonicus) developed progressive paralytic symptoms within one hour of the bite. After seeking traditional treatment her condition deteriorated and when she arrived at hospital 6 h after the bite she was drowsy, with bilateral ptosis and signs of aspiration pneumonia (a complication of traditional treatment). She developed an anaphylactic reaction after antivenom treatment and, despite treatment, had a cardio-respiratory arrest. She was resuscitated and mechanically ventilated, but remained deeply unconscious until her death 90 h after the bite. B. ceylonicus is endemic in Sri Lanka, is common in some areas, and could be mistaken for the common krait (B. caeruleus). It is doubtful whether any existing antivenom is effective against its venom.